Perancangan Materi Ajar Penggunaan Alat Ukur Listrik Dan Elektronika Berbasis Adobe Flash Cs6 Jurusan Teknik Audio Dan Video Di SMK N 1 SUMBAR - Elfa Rianti; Putra Jaya (Jurnal Teknologi Informasi dan Pendidikan, 2021)
The purpose of this study was to determine the feasibility of designing teaching materials using adobe flash CS6-based electrical and electronic measuring instruments and the increase in student learning outcomes in basic electricity and electronics (DLE) subjects in the audio and video engineering department at SMK N 1 West Sumatra. The method used in this study uses the waterfall model. The waterfall model consists of 1) Define, 2) Design, 3) Development, 4) Testing. The research was conducted at SMK N 1 West Sumatra. Data collection techniques are validation from material experts, media experts, practicality tests for teachers and students, then to find out student learning outcomes, test tests are conducted for students. The results of the validation of the material get a mean score of 4.8 with a very feasible category, the results of the validation of media experts get a mean score of 4.83 with a very feasible category, the results of the practicality test of the teacher get a score of 4.7 with the very practical category and 94% presentation, the results of the practicality test students get a mean score of 4.04 with the practical category and 80.8% presentation, and the learning outcomes of X TAV students get a mean score of 75.6 with a presentation of 83.7% and the category is very good. The data obtained shows that the design of teaching materials using electric and electronic measuring instruments based on Adobe Flash CS6 is valid, practical and there is an increase in student learning outcomes.